About directions of overcoming of the modern crisis States of the economy of Russia - V. Serov (Publishing House of the State University of Management, 2016)
In the general methodical plan the offer on the organisation of system of the indicative analysis and regulation of volumes of output is proved and reveals and is industrial-economic activities the enterprises and the organisations of real sector of economy, as organizational tool of the permission of crisis positions in economy. In the concrete plan author's offers in directions and ways of overcoming of the modern crisis phenomena in economy of Russia are stated.